Determining Electrode Placement for Transcranial Direct Current Stimulation: A Comparison of EEG- Versus TMS-Guided Methods. (November 2017) - Rich, Tonya L.; Menk, Jeremiah S.; Rudser, Kyle D.; Chen, Mo; Meekins, Gregg D.; Peña, Edgar; Feyma, Timothy; Bawroski, Kay; Bush, Christina; Gillick, Bernadette T.
Transcranial direct current stimulation (tDCS) is increasingly researched as an adjuvant to motor rehabilitation for children with hemiparesis. The optimal method for the primary motor cortex (M1) somatotopic localization for tDCS electrode placement has not been established. The objective, therefore, was to determine the location of the M1 derived using the 10/20 electroencephalography (EEG) system and transcranial magnetic stimulation (TMS) in children with hemiparesis (CWH) and a comparison group of typically developing children (TDC). We hypothesized a difference in location for CWH but not for TDC. The 2 locations were evaluated in 47 children (21 CWH, 26 TDC). Distances between the locations were measured pending presence of a motor evoked potential. Distances between the EEG and TMS locations that exceeded the 2.5 cm × 2.5 cm rubber electrode area are reported in percentages [95% confidence interval] in CWH—nonlesioned hemisphere was 68.8% [41.3-89.0], lesioned: 85.7% [57.2-98.2]; TDC—dominant hemisphere 73.9% [51.6-89.8], nondominant: 82.6% [61.2-95.0]. Distances that exceeded the 3 × 5 cm electrode sponge area in CWH—nonlesioned was 25.0% [7.3-52.4], lesioned was 28.6% [8.4-58.1]; TDC—dominant was 52.2% [30.6-73.2], nondominant was 43.5 [23.2-65.5]). Distances that exceeded the 5 × 7 cm electrode sponge area in CWH—nonlesioned was 18.8% [4.0-45.6] and lesioned was 21.4% [4.7-50.8]; TDC—dominant was 21.7% [7.5-43.7] and nondominant was 26.1% [10.2-48.4]. Individual variability in brain somatotopic organization may influence surface scalp localization of underlying M1 in children regardless of neurologic impairment. Findings suggest further investigation of optimal tDCS electrode placement. EEG and TMS methods reveal variability in localizing M1 in children regardless of stroke diagnosis. This study was registered onclinicaltrials.gov NCT02015338.